2006
DOI: 10.1111/j.1875-595x.2006.tb00086.x
|View full text |Cite
|
Sign up to set email alerts
|

A practice-based evaluation of the handling of a new self-adhesive universal resin luting material

Abstract: The new material achieved ratings for ease of use superior to the pre-study resin-based and conventional luting materials in the dental practices of 13 UK dental practitioners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 5 publications
0
17
0
2
Order By: Relevance
“…Burke and colleagues conducted a practice‐based evaluation of the handling of a new self‐adhesive universal resin luting material. One hundred forty‐four restorations were cemented using a self‐adhesive resin luting material that was rated higher by the evaluators for ease of use, convenience, and handling than resin‐based and conventional luting agents 3 . In general, our data indicate that the capsule mixing system produces a stronger bond and better retention than other mixing systems that may, in critical situations, influence clinical success.…”
Section: Are Self‐adhesive Cements Clinically Successful?mentioning
confidence: 87%
“…Burke and colleagues conducted a practice‐based evaluation of the handling of a new self‐adhesive universal resin luting material. One hundred forty‐four restorations were cemented using a self‐adhesive resin luting material that was rated higher by the evaluators for ease of use, convenience, and handling than resin‐based and conventional luting agents 3 . In general, our data indicate that the capsule mixing system produces a stronger bond and better retention than other mixing systems that may, in critical situations, influence clinical success.…”
Section: Are Self‐adhesive Cements Clinically Successful?mentioning
confidence: 87%
“…Several studies have demonstrated the limited ability of SARCs to demineralize and dissolve the smear layer to reach the underlying dentin. [1][2][3][4][5][6][7] This limitation is attributed to the high viscosity 8 of the cements and the buffering effect that takes place during their setting reaction. 9 The smear layer on the dentin substrate of the present study was produced using 600-grit silicon carbide paper, and it has previously been demonstrated that smear layers produced using this method are thicker than layers obtained using a carbide bur (approximately 1.8 µm).…”
Section: Discussionmentioning
confidence: 99%
“…Co‐ordinated assessments of new materials by practitioner‐based research groups, typically teamed with the research expertise available in academic institutions, are becoming more common. Perhaps the first such group was the Clinical Research Associates (CRA), based in the U.S. More recently, other practice‐based research networks have evolved, including Practice‐based Research in Oral Health (PROH) in the U.S. (88) and the Product Research and Evaluation by Practitioners Panel (PREP) based in the U.K. (89–91).…”
Section: The Clinical Considerationsmentioning
confidence: 99%
“…A UK evaluation by thirteen members of the PREP Panel used a 21‐question questionnaire designed to provide information on the handling and ease of use of RelyX Unicem and the comparison of this material with pre‐study cementation materials (91). A total of 144 restorations were placed in the study, and RelyX Unicem was rated higher by the evaluators for ease of use than both the pre‐trial resin‐based cement and ‘conventional’ cements.…”
Section: The Clinical Considerationsmentioning
confidence: 99%